Preparation and Characterization of Flexible Asymmetric Supercapacitors Based on Transition-Metal-Oxide Nanowire/Single-Walled Carbon Nanotube Hybrid Thin-Film Electrodes - Chen, Po-Chiang; Shen, Guozhen; Shi, Yi; Chen, Haitian; Zhou, Chongwu (ACS nano, 2010)
In the work described in this paper, we have successfully fabricated flexible asymmetric supercapacitors (ASCs) based on transition-metal-oxide nanowire/single-walled carbon nanotube (SWNT) hybrid thin-film electrodes. These hybrid nanostructured films, with advantages of mechanical flexibility, uniform layered structures, and mesoporous surface morphology, were produced by using a filtration method. Here, manganese dioxide nanowire/SWNT hybrid films worked as the positive electrode, and indium oxide nanowire/SWNT hybrid films served as the negative electrode in a designed ASC. In our design, charges can be stored not only via electrochemical double-layer capacitance from SWNT films but also through a reversible faradic process from transition-metal-oxide nanowires. In addition, to obtain stable electrochemical behavior during charging/discharging cycles in a 2 V potential window, the mass balance between two electrodes has been optimized. Our optimized hybrid nanostructured ASCs exhibited a superior device performance with specific capacitance of 184 F/g, energy density of 25.5 Wh/kg, and columbic efficiency of ∼90%. In addition, our ASCs exhibited a power density of 50.3 kW/kg, which is 10-fold higher than obtained in early reported ASC work. The high-performance hybrid nanostructured ASCs can find applications in conformal electrics, portable electronics, and electrical vehicles.